Poverty Alleviation Strategy Through Leading Sector (Efficient: Indonesian Journal of Development Economics, 2022)
This study aims to identify the leading sector and poverty alleviation strategies in Kulon Progo Regency. The method used in this study is the Location Quotient (LQ) analysis method, Shift Share analysis, and SWOT analysis. The results showed that the leading sectors in Kulon Progo Regency consisted of the mining and quarrying sector; water supply, waste management, waste and recycling sectors; construction sector; wholesale and retail trade sector; repair of cars and motorcycles; transportation and warehousing sector; government administration, defense, and mandatory social security sectors. The results of the SWOT analysis show that the strategy that can be implemented to reduce poverty through the leading sector in Kulon Progo Regency is by utilizing the S-O strategy which includes creating a people-based economy by optimizing the economic potential of the leading sector, utilizing the multiplier effect of the construction of Yogyakarta International Airport, implementing the spirit of self-defense. -Buy Kulon Progo and take advantage of the 84 waste banks in Kulon Progo Regency. Penelitian ini bertujuan untuk mengidentifikasi sektor unggulan, dan strategi pengentasan kemiskinan melalui sektor unggulan di Kabupaten Kulon Progo. Metode yang digunakan dalam penelitian ini yaitu metode analisis Location Quotient (LQ), analisis Shift Share dan analisis SWOT. Hasil penelitian menunjukkan bahwa sektor unggulan di Kabupaten Kulon Progo terdiri dari sektor pertambangan dan penggalian; sektor pengadaan air, pengelolaan sampah, limbah, dan daur ulang; sektor konstruksi; sektor perdagangan besar dan eceran; reparasi mobil dan sepeda motor; sektor trasportasi dan pergudangan; sektor administrasi pemerintahan, pertahanan, dan jaminan sosial wajib. Hasil analisis SWOT menunjukkan bahwa strategi yang dapat dilaksanakan dalam upaya pengentasan kemiskinan melalui sektor unggulan di Kabupaten Kulon Progo yaitu dengan memanfaatkan strategi S-O, meliputi menciptakan perekonomian berbasis kerakyatan dengan mengoptimalkan potensi ekonomi dari sektor unggulan, memanfaatkan multipier effect pembangunan Bandara Yogyakarta International, menginplementasikan semangat bela-beli Kulon Progo dan memanfaatkan 84 bank sampah yang ada di Kabupaten Kulon Progo.